2017
DOI: 10.1002/2327-6924.12378
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioner screening for childhood adversity among adult primary care patients

Abstract: Background and purpose Researchers have demonstrated an association between experiencing childhood abuse and multiple chronic health conditions in adulthood, yet this evidence has not been routinely translated to practice. The purpose of this research study was to examine nurse practitioner (NP) practices, skills, attitudes, and perceived barriers associated with screening adult patients for childhood abuse to determine the extent to which evidence of the association between childhood abuse and negative health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 30 publications
1
52
3
Order By: Relevance
“…A Level II systematic review of health consequences of ACE provided evidence for the necessity of screening for ACE in the primary care setting (Kalmakis & Chandler, 2015). Based on the work of Kalmakis and Chandler (2016), two pilot translational research studies demonstrated the impact of ACE on primary care patients, contributing additional evidence for the necessity of screening for ACE to reduce negative health consequences in the primary care setting (Aponte, 2017, Kalmakis, et al, 2018, & Shafer, 2017.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A Level II systematic review of health consequences of ACE provided evidence for the necessity of screening for ACE in the primary care setting (Kalmakis & Chandler, 2015). Based on the work of Kalmakis and Chandler (2016), two pilot translational research studies demonstrated the impact of ACE on primary care patients, contributing additional evidence for the necessity of screening for ACE to reduce negative health consequences in the primary care setting (Aponte, 2017, Kalmakis, et al, 2018, & Shafer, 2017.…”
Section: Resultsmentioning
confidence: 99%
“…A literature review for SBIRT, trauma, and motivational interviewing (MI) was conducted to contribute additional evidence for the use of three-phase protocol developed by Kalmakis and Chandler (2016) for this study. SBIRT and MI have been extensively studied and are utilized in a variety of healthcare settings.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations